Producing the organic Roselle crop and improving its growth, fruiting, and chemical constituents using a biostimulant compound. - Sudad K. Al-Taweel; Aws A. Mohammed; R.A.A. Al-Asadi (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Roselle (Hibiscus sabdariffa L.) is an annual shrub with a multipurpose crop with great economic potential to increase the income of farmers and processors in some countries worldwide from the export and local markets. Therefore, two successive seasons (2020 and 2021) were conducted to investigate how fertilization either organic manure or chemical fertilizer and foliar application of Appetizer (App) and their combination could affect the plant growth, yield, and chemical composition of Roselle plant. The treatments used App. solely at 3 rates (0, 4, 6 g L-1), in interaction with the total dose of organic manure or chemical fertilizer, or with a half dose of both fertilizers. Also, values were tested for each fertilizer applied solely at a total dose and in interaction at a half dose. It was found that spraying Roselle plants with App positively increased all parameters studied over the control. However, such an increase was greatly enhanced when the App. was combined with fertilization. Whereas, the highest records of growth characters, the chemical constituents of roselle plant, ascorbic acid, and carbohydrate resulted from half doses of chemical and organic manure with 4 and 6 g L-1 of App. While the highest values of all yield characters were obtained from the combination of chemical fertilizer at total dose and App at 4 g L-1, respectively, it was discovered, as well, that organic manure applied solely or combined with App gave high values that were so close and superior, in some cases, to those of chemical fertilizer. Hence, organically speaking, it is recommended that if there are fewer harmful and healthier products in agriculture, organic manure, either alone or combined with App, is still of high value for plant yield, especially when integrated with 4g L-1 App.